Differential Hyperphosphorylation of Tau-S199, -T231 and -S396 in Organotypic Brain Slices of Alzheimer Mice. A Model to Study Early Tau Hyperphosphorylation Using Okadaic Acid - Foidl, Bettina M.; Humpel, Christian (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder of the brain, characterized by extracellular aggregation of beta-amyloid (Aβ) and hyperphosphorylation of tau causing intraneuronal neurofibrillary tangles. There is urgent need to study the interactions between Aβ and tau, especially to solve the question of the pathological cascade. In the present study, we aim to develop a model of organotypic brain slices in which both plaque and tau pathology can be examined. Organotypic brain slices (150 µm thick, coronal, at the hippocampal level) from adult (9 month) wildtype (WT, C57BL/6N) and transgenic AD mice (TG, APP_SweDI) were cultured for 2 weeks. To induce tau hyperphosphorylation 100 nM okadaic acid (OA), 10 µM wortmannin (WM) or both were added to the slices. Hyperphosphorylation of tau was tested at tau-S199, tau-T231 and tau-S396 using Western blot. Our data show that in transgenic mice with plaques a 50 kDa fragment of tau-S396 was hyperphosphorylated and that OA induced hyperphosphorylation of tau-S199. In wildtype mice (without plaques) OA caused hyperphosphorylation of a 50 kDa and a 38 kDa tau-T231 form and a 25 kDa tau-S396 fragment. The NMDA antagonist MK801 (1 µM) did not block these effects. Immunohistochemistry showed diffuse increased tau-S396 and tau-T231-like immunoreactivities at the hippocampal level but no formation of neurofibrillary tangles (NFTs). Confocal microscopy indicated, that pTau-T231 was preferentially located in cytoplasma surrounding nuclei whereas pTau-S396 was found mainly in nerve fibers and strongly associated with plaques. In conclusion we provide a novel in vitro model to study both plaque and tau hyperphosphorylation but not NFTs, which could be useful to study pathological processes in AD and to screen for drugs.